Optimisation of Compressive Strength of Fast Track Concrate Using Superplasticizer and Accelerator as Bridge Slab of Upper Structure - Firdaus, Arga Agung; Rahman, Aulia; Qomariah, Qomariah (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
Fast track concrete is designed to accelerate the construction process, particularly in pouring operations. This study aims to determine the optimal early-age compressive strength of concrete applied to bridge decks, where flexural strength testing will be conducted. The admixtures used are superplasticizer (SP) and accelerator (AC). The dosages used are 0.8% and 1.2% of cement weight for superplasticizer, and 2.7% and 4.5% of cement weight for accelerator. Compressive strength testing is conducted at 6 hours, 1 day, 7 days, and 28 days after casting.The mix combination used includes SP 0.8% – AC 2.7%, SP 0.8% - AC 4.5%, SP 1.2% - AC 2.7%, and SP 1.2% - AC 4.5%. The concrete design uses a strength of fc’30 MPa with cylindrical test specimens. The results show that compressive strength increases with age. Flexural strength testing is applied to a bridge deck slab measuring 1 x 0.5 x 0.1 m, tested at 3 days of age. The concrete mix uses fc’30 with an SP dosage of 1.2% and AC dosage of 4.5% of cement weight. In the flexural test, the average load-bearing capacity is 40 kN.